Influence Of Project Based Learning Models Comics On Student Characters Pancasila Class V Students - Musdalifah Ali; Supriadi Supriadi; Erwin Nurdiansyah (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
This research is driven by the urgent need for innovative learning strategies in elementary schools to improve students' Pancasila character, especially in the context of science development with the aim of testing the effectiveness of the comic-based Project-Based Learning (PjBL) model in improving students' Pancasila character in elementary schools. This model was chosen because it is able to combine contextual project activities with visual media that attracts students' interest. This study uses a quantitative approach with a one-group pretest-posttest design, involving 30 fifth-grade students at SDN 127 Inpres Moncongloe as subjects. The instruments used include observation, tests, interviews, and documentation. The pretest results showed an average student character score of 53.95, while in the posttest it increased to 80.20. In addition, the level of teacher and student activity during the implementation of this model exceeded 90%, indicating a high level of engagement. Inferential statistical analysis using a t-test showed a significant difference between the conditions before and after the implementation of the learning model. This finding indicates that the comic-based PjBL model is not only effective in improving academic understanding but also in instilling character values ??such as mutual cooperation, independence, and creativity. This study recommends the use of comics as an engaging and educational alternative learning medium to strengthen PPKn learning at the elementary level.